2003
DOI: 10.1177/160940690300200201
|View full text |Cite
|
Sign up to set email alerts
|

‘Clear as Mud’: Toward Greater Clarity in Generic Qualitative Research

Abstract: We have observed a growth in the number of qualitative studies that have no guiding set of philosophic assumptions in the form of one of the established qualitative methodologies. This lack of allegiance to an established qualitative approach presents many challenges for "generic qualitative" studies, one of which is that the literature lacks debate about how to do a generic study well. We encourage such debate and offer four basic requirements as a point of departure: noting the researchers' position, disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
576
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 715 publications
(614 citation statements)
references
References 42 publications
4
576
0
7
Order By: Relevance
“…For professional ethics the characteristics were identified as objectivity, impartiality, full disclosure, openness, confidentiality, due diligence, fidelity to professional responsibilities and the avoidance of potential or apparent conflict of interest. Yekta et al also found similar results in that codes of ethics do not have a significant impact on reporting wrongdoing in organizations [13]. They suggest that codes of ethics can work effectively and will prove positive in the reporting of wrongdoing if an organization invests time and effort in building good employee relationships.…”
Section: Literature Reviewsupporting
confidence: 63%
“…For professional ethics the characteristics were identified as objectivity, impartiality, full disclosure, openness, confidentiality, due diligence, fidelity to professional responsibilities and the avoidance of potential or apparent conflict of interest. Yekta et al also found similar results in that codes of ethics do not have a significant impact on reporting wrongdoing in organizations [13]. They suggest that codes of ethics can work effectively and will prove positive in the reporting of wrongdoing if an organization invests time and effort in building good employee relationships.…”
Section: Literature Reviewsupporting
confidence: 63%
“…Penelitian ini menggunakan pendekatan penelitian kualitatif dengan jenis penelitian basic or generic (Paisley dan Reeves, 2001), yang oleh Caelli, Ray, dan Mill (2003) …”
Section: Metodeunclassified
“…We adopted a generic qualitative descriptive research approach (Caelli, Ray, & Mill, 2003), providing a process to allow participants to explore their lived experiences and seeking to understand their views of delivering health and social care to PLWH. This was the most appropriate approach to provide a valued understanding of participants' perceptions and to contribute to evidence-based health and social care (Smith, Becker, & Cheater, 2008).…”
Section: Methodsmentioning
confidence: 99%